(untitled) (Western European Journal of Linguistics and Education, 2024)
This article explores the comparative advantages and disadvantages of online and offline education methods, particularly in the context of the COVID-19 pandemic. Through a survey conducted among 105 graduates of UzSWLU, the study examines preferences and impacts on various aspects of student development, including time management, selfdiscipline, networking, and health